THE CURRICULUM DEVELOPMENT FOR ENHANCING CREATIVE THINKING BY USING STEAM EDUCATION IN SCIENCE AND TECHNOLOGY SUBJECT FOR GRADE 2 STUDENTS - Plewthong , Preeyanuch; Sirichaisin, Kedthip (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
The objectives of this research are to create and find indexes on the effectiveness of courses to promote creativity by using the steam education learning management science and technology learning subject group for Prathomsuksa 2students.To study creativity science and technology learning subject group of students in Prathomsuksa 2 by using steam education learning management. The sample group used in this research were 40 students in the second semester of 2021 academic year at Jae Hom kindergarten, Jae Hom District, Lampang Province under Lampang Primary Educational Service Area Office Region 3. The research tools are 1) Course 2) Course manual and 3) Creativity assessment from for Prathomsuksa 2 students, the data was analyzed by finding the percentage, mean, standard deviation and t-test dependent samples statistics. The results of the research showed that 1) The creation and finding of effectiveness of the curriculum average suitability of the curriculum was at a high level course manual the average of the suitability of the curriculum used in the curriculum was at the highest level. It has an efficiency index of 0.6563. 2)The results of studying of using the curriculum a study of the results of using a curriculum to promote creativity by using the steam education learning management science and technology learning subject group for Prathomsuksa 2 students, it was found that the student ‘scores after school were significantly higher than specified criteria at the .05 level, which was in line with the hypothesis.